Adequate Correlation between the Physical and Mechanical Properties of Glass Foam - Lucian Paunescu; Sorin Mircea Axinte; Marius Florin Dragoescu; Felicia Cosmulescu (Newinera Publisher, 2021)
The paper presents experimental results obtained in the manufacturing process of a glass foam by adequate correlation between its physical and thermal properties (density, porosity, thermal conductivity) and mechanical (compressive strength) by a slight controlled overheating of the foamed material. Using a powder mixture of glass waste (87-91.5 %), coal fly ash (3-9 %) and silicon carbide (4-5.5 %) microwave heated at 935-975 ºC by this unconventional technique, constituting the originality of the work, was obtained a glass-ceramic foam with moderate compressive strength (1.8-2.6 MPa) and very low thermal conductivity (0.058-0.070 W/m·K). The material overheating generated a homogeneous porous structure characterized by closed cells with relatively large dimensions (without the tendency to join neighboring cells) making it difficult to transfer heat across the material. The foamed product is suitable for the manufacture of thermal insulation blocks for the inner or outer walls of the building without excessive mechanical stress, being an advantageous alternative by comparison with known types of polymeric or fiberglass thermal insulation materials.